Fuzzy Logic Control Design on Buck Converter For Thermo Electric Air Cooler Power Supply - Muhammad Wildan Alim; Novie Ayub Windarko; Renny Rakhmawati (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
The air conditioning system that is commonly used today is an Air Conditioner (AC). Unfortunately, this system is a big contributor to global warming. Often times, we find that air conditioners are only used to cool only a small part of a room for individual comfort. Therefore, a new breakthrough is needed from a cooling system that does not use chemicals so that it is environmentally friendly, namely using the Thermo Electric Cooler (TEC) cooling module which utilizes the cold side of the Thermo Electric Cooler (TEC). The size of the DC input voltage on the Thermo Electric Cooler (TEC) is adjusted using a buck converter with fuzzy control. When the buck converter closed loop condition with fuzzy control has a rise time value, the settling time and error percentage have a relatively better value than the open loop condition. When the buck converter set point 40V, the minimum water temperature in the air cooler can be reached 220C, when the buck converter set point is 48V the minimum water temperature in the water cooler can be reached 190C, and when the buck converter set point is 56V the minimum water temperature in the air cooler can be reached 180C. When the water cooler uses air cooler by Peltier, the input air temperature and output air temperature decrease in temperature around 10C. this is caused by the evaporative effect caused by water cooled by the peltier.Keywords: buck converter, cooler, fuzzy, thermo electric cooler.